2014
DOI: 10.1007/s00062-014-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Imaging of Viscoelastic Properties of Intracranial Tumours by Multi-Frequency Magnetic Resonance Elastography

Abstract: In this pilot study, while analysing the viscoelastic constants of various intracranial tumour entities with an improved spatial resolution, it was possible to characterize intracranial tumours by their mechanical properties. We were able to clearly delineate meningiomas from intraaxial tumours, while for the latter group an overlap remains in viscoelastic terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 46 publications
4
92
0
Order By: Relevance
“…phase angle and loss tangent) have been shown to have the potential to distinguish meningiomas from glioblastomas, anaplastic astrocytomas, cerebral metastases and abscess in 27 patients with intracranial tumors (30). Perepelyuk et al also found that the ratio G ″/ G ′ (loss tangent) to be sensitive to very early onset of liver injury in an ex vivo CCl 4 mouse model (31).…”
Section: Discussionmentioning
confidence: 99%
“…phase angle and loss tangent) have been shown to have the potential to distinguish meningiomas from glioblastomas, anaplastic astrocytomas, cerebral metastases and abscess in 27 patients with intracranial tumors (30). Perepelyuk et al also found that the ratio G ″/ G ′ (loss tangent) to be sensitive to very early onset of liver injury in an ex vivo CCl 4 mouse model (31).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that primary brain tumors have a uniform loss of dissipative behavior and that the tumor mechanical properties are altered with increasing malignancy 18 . Similarly, another study investigated the mechanical properties of GBMs using MRE and found that the majority of GBMs were softer than normal brain 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of using MRE to evaluate the viscoelastic properties of brain tumors including gliomas, where brain tumors were mainly softer than normal brain and benign variants, however some tumors are stiffer than normal brain 17 and GBMs were the softest brain tumors when compared to meningiomas, vestibular schwannomas, and metastases 18, 19 . Additional work demonstrated that viscoelastic properties of GBMs were dependent on composition (e.g., necrosis or cystic cavities) and that the mechanical properties were heterogeneous with both stiff and soft regions 17, 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Although many of these studies have shown that tumors are stiffer than normal brain (Xu et al, 2007;Scholz et al, 2007Scholz et al, , 2005Chauvet et al, 2015), some have shown the opposite (Reiss- Zimmermann et al, 2015;Streitberger et al, 2014), and determination of stiffness differences between tumor grades has been inconclusive using this technique. Consistent with observations of stiffening of brain tumors, increased diffusion of water within a tumor, as measured by magnetic resonance imaging (MRI), is prognostic of poor outcome and is correlated with increased expression of ECM genes whose products are expected to stiffen a tissue (Pope et al, 2012(Pope et al, , 2009.…”
Section: Mechanical Properties Of Brain Tumor Subtypesmentioning
confidence: 99%